SERVQUAL MODEL DALAM MEMULIHKAN KEPUASAN MAHASISWA POLITEKNIK DI KOTA MEDAN PADA POST PANDEMIC WORLD - Nugroho, Ngajudin; Ciamas, Elserra Siemin; Hutabarat, Fauzi Akbar Maulana (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research Aim: This study aims to develop a SERVQUAL model to restore student satisfaction in polytechnic institutions in Medan City through campus facilities in the post-pandemic period. Approach: The research uses a quantitative approach with descriptive statistical analysis and Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from polytechnic students in Medan City using purposive sampling techniques. Research Finding: The results indicate that SERVQUAL significantly influences polytechnic student satisfaction through campus facilities in the post-pandemic era. The quality dimensions of tangibility, reliability, responsiveness, assurance, and empathy contribute to improving overall satisfaction. Theoretical Contribution/Originality: This study extends the application of the SERVQUAL model in higher education by integrating post-pandemic contextual factors, offering new insights into the determinants of student satisfaction in vocational institutions. Practitioner/Policy Implication: Findings provide practical implications for educational managers to enhance academic service quality and campus facilities, thereby improving educational competitiveness and institutional reputation after the pandemic. Research Limitation: This study is limited to polytechnic institutions in Medan City, so future research should include broader geographic coverage and comparative analysis across various higher education institutions.